G53(P) Leading the way with nurse led discharges. (May 2019) - Bunn, A; Srinivas, J; Cook, R; Leigh, H; Campbell, D
Abstract : Background: Nurse led discharges (NLD) were introduced into a district general teaching hospitals paediatric assessment unit (PAU) with the aim to make patient flow more efficient, thus allowing for increased departmental capacity. Currently, there are no national guidelines for paediatric NLD and therefore, we utilised similar practices from adult guidelines. For every patient on the pathway our criteria encompassed; completion of NLD paperwork, discharge summaries completed prior to inclusion on the pathway, discharge criteria in accordance with trust policy, and appropriate discharge advice and safety netting communicated prior to discharge. Aim: The initiation of nurse led discharges was audited to identify how frequently and effectively they were being utilised, as well as recognise common conditions and discharge criteria utilised. Methods: We used a purposive sampling method and included all patients from 01/11/16 to 31/01/17 who were on PAU and put onto the NLD pathway. Data was collected electronically utilising MRN numbers to maintain confidentiality. Results: During this time frame; 1792 patients presented to PAU, of which 4% were placed onto the NLD pathway (70/1792). The most common 3 conditions identified were viral induced wheeze (32%), respiratory tract infections (21%) and tonsillitis (13%). To ensure this method of discharging patients was safe, we also audited re-admissions and found of the 70 patients, 7% were subsequently readmitted. Auditing the agreed standards set out, 100% had NLD paperwork completed, 92% had discharge summaries completed prior to discharge, 95% had criteria in accordance with trust policy, and 87% had appropriate discharge advice and safety netting documented prior to discharge. Discussion: These results were presented at a departmental meeting where nursing and medical staff opted to continue using this policy with few modifications. Going forward, we plan to increase awareness and utilisation of the NLD pathway, followed by re-auditing the process and extending NLD's to inpatients. In conclusion, this audit showed NLD could decrease repeated medical reviews, increase patient satisfaction with timely discharges, and hence be an effective approach to improve patient flow specifically during busy winter periods.